Etnomatematika Historical Building “Taman Mayura” dan Implementasinya dalam Pengembangan Kemampuan Numerasi Siswa Sekolah Dasar - Musliana, Rini; Hulpiana, Titik; Putri, Dwi; Awinda, Sephia; Rahmania, Livia Alda; Nurmawanti, Iva (Plusminus: Jurnal Pendidikan Matematika, 2024)
Etnomatematika sangat penting untuk memberikan pembelajaran kontekstual. Riset ini bertujuan menggali dan mendeskripsikan etnomatematika Historical Building di Taman Mayura dan mengetahui pengaruhnya terhadap kemampuan numerasi siswa sekolah dasar. Desain riset ini menggabungkan penelitian kualitatif dan kuantitatif melalui metode observasi, deep interview, dokumentasi, dan tes. Teknik analisis data menggunakan Milles dan Huberman dan uji paired sample t-test. Hasil riset menyatakan, terdapat 6 bangunan bersejarah di Taman Mayura, yakni bale kambang, kolam (telaga), bale pererenan, bale lodji, pura jagat nata, dan pura kelepug. Berbagai jenis bangun datar ditemukan pada struktur bangunan tersebut, seperti bangun datar segiempat, segitiga dan segibanyak. Berdasarkan hasil uji hipotesis, dibuktikan bahwa ada pengaruh signifikan implementasi etnomatematika Historical Building “Taman Mayura” terhadap perkembangan kemampuan numerasi siswa kelas 4 SDN 38 Cakranegara. Ethnomathematics is essential for providing contextual learning. Therefore, this research aims to explore and describe the ethnomathematics of the Historical Building in Mayura Park and determine the influence of ethnomathematics on the numeracy ability of elementary school students. This research design combines qualitative research and quantitative research through observation methods, deep interviews, documentation, and tests. The data analysis technique was carried out based on the opinions of Milles and Huberman and the paired sample t-test. The results of the research stated that there are 6 historical buildings in Mayura Park, namely bale kambang, pond (lake), bale pererenan, bale lodji, jagat nata temple, and kelepug temple. Various types of flat buildings are found in these building structures, such as quadrilateral, triangular and polygonal flat buildings. Based on the results of the hypothesis test, it is proven that there is a significant influence of the ethnomathematics implementation of the Historical Building "Taman Mayura" on the development of numeracy skills of grade 4 students of SDN 38 Cakranegara.